The matchmaker; a farce in four acts. - Wilder, Thornton, 1897-1975 (S. French, 2017)
"Horace Vandergelder, a wealthy merchant in 19th Century Yonkers, NY, decides to take a wife and employs a matchmaker, Mrs. Dolly Levi. Dolly subsequently becomes involved with two of Vandergelder's clerks, several lovely ladies, and the headwaiter at an expensive restaurant where this swift farce runs headlong into hilarious complications. After everyone gets straightened out romantically, Vandergelder finds himself affianced to the astute Dolly Levi herself."--Publisher's description.